12+5m=-3

Simple and best practice solution for 12+5m=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+5m=-3 equation:


Simplifying
12 + 5m = -3

Solving
12 + 5m = -3

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 5m = -3 + -12

Combine like terms: 12 + -12 = 0
0 + 5m = -3 + -12
5m = -3 + -12

Combine like terms: -3 + -12 = -15
5m = -15

Divide each side by '5'.
m = -3

Simplifying
m = -3

See similar equations:

| x-(8x+5)=15+2(11-7x) | | 3+2x=3(2x+4)-5(x-2) | | 3x-(8-x)=5(3-x)+4 | | -7+2x=-25-x | | x-(8-x)=5(3-x)+4 | | 10+12=-34+x | | 2x+10-7x=3(x-5)+1 | | 3*(x+2)=3x+32 | | 7(2x+1)=5x+16 | | 9x+8+2x+6=7x+2 | | 8x-5x=8 | | 10p-4=86 | | -7+8x-19=15+3(x-17) | | 5/m=8/6 | | 2[t+6]-1=9 | | 3/n=10/7 | | x+8(12-x)=7x-(5x-42) | | 6/a=5/7 | | -16=-4[v+3] | | 1/2-3x=-1/2 | | -4+5x=36 | | x+8(12-x)=7x(5x-42) | | -8x-5x-96=60 | | 8/3=n/4 | | x-7x-61=23 | | 7=2[r+6]-5 | | r(x)=x(13-0.04x) | | -15=10+5v | | -2x-10+3x=9 | | 62=-7v-1 | | 2[w+2]=10 | | 9x^4/3x^3 |

Equations solver categories